CHANGE IN SOCIETY IN MODERN DIGITAL AGE SOCIETIES - Bernadus Wibowo Suliantoro; Farida Asy'ari; Loso Judijanto; Firmansyah; Abdul Rozak (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
This article provides an overview of social change in modern society, covering drivers, types of change, impacts, and challenges faced. Factors such as technological development, globalization, urbanization, demographic change, and cultural change play a major role in social change. Social change can affect social structures, value systems, individual behaviour, and social group dynamics. Impacts include new opportunities and instability, while challenges include socio-economic gaps, meeting basic needs, cultural integration, changing social identities, and eradicating access to resources. This journal provides important insights for policymakers, researchers, and social practitioners in the face of ever-increasing social change.